Adipose Natural Killer Cells Regulate Adipose Tissue Macrophages to Promote Insulin Resistance in Obesity - Lee,B-C; Kim,M-S; Pae,M; Yamamoto,Y; Eberle,D; Shimada,T; Kamei,N; Park,H-S; Sasorith,S; Woo,JR; You,J; Mosher,W; et al. (Cell Metabolism, 2016)
Obesity-induced inflammation mediated by immune cells in adipose tissue appears to participate in the pathogenesis of insulin resistance. We show that natural killer (NK) cells in adipose tissue play an important role. High-fat diet (HFD) increases NK cell numbers and the production of proinflammatory cytokines, notably TNFα, in epididymal, but not subcutaneous, fat depots. When NK cells were depleted either with neutralizing antibodies or genetic ablation in E4bp4+/− mice, obesity-induced insulin resistance improved in parallel with decreases in both adipose tissue macrophage (ATM) numbers, and ATM and adipose tissue inflammation. Conversely, expansion of NK cells following IL-15 administration or reconstitution of NK cells into E4bp4−/− mice increased both ATM numbers and adipose tissue inflammation and exacerbated HFD-induced insulin resistance. These results indicate that adipose NK cells control ATMs as an upstream regulator potentially by producing proinflammatory mediators, including TNFα, and thereby contribute to the development of obesity-induced insulin resistance.